Prevalence and Antimicrobial Susceptibility Patterns of Methicillin-Resistant Staphylococcus Aureus (MRSA) in Patients from District Bahawalpur - Munawer, Muhammad Faizan; Shahzad, Khawar Ali; Marryum, Munazzah; Saleem, Mavra; Ramzan, Shabana (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
Methicillin-resistant S. aureus (MRSA) is an opportunistic bacterium causing a lot of infections, including infections of skin and soft tissues, endocarditis, pneumonia and bacteremia leading to death globally. This study aimed to determine the Methicillin-resistant S. aureus (MRSA) incidence and the antimicrobial pattern of MRSA among patients at a tertiary care hospital of Bahawalpur. Clinical samples (blood, sputum, catheter tips, pus, blood, urine, body fluid, wound, nasal and throat swabs) were collected from the hospital and transported to the microbiology laboratory. Culture and sensitivity testing was done in the laboratory to find out the antimicrobial susceptibility of S. aureus according to CLSI guidelines 2021. Among 622 collected specimens, 82 S. aureus isolates were found, and MRSA was found in 55 samples. MRSA was more prevalent in males as compared to females. In urine, a high incidence of MRSA was found. In age groups, a high prevalence was seen in the 61–70-year age group, and the lowest prevalence was seen in the 0–10-year age group. In OPD, the S. aureus prevalence was 39%. Among wards, the highest prevalence of MRSA was recorded in the ICU. Among S. aureus isolates, high resistance was shown by penicillin, cefoxitin and Sulphamethoxazole. Linezolid was found to be highly susceptible to S. aureus isolates. Linezolid, vancomycin, Fusidic acid, teicoplanin and clindamycin were the most effective antibiotics for treating infection caused by MRSA. The current study also noticed high resistance of bacteria to numerous antibiotics, revealing the significance of monitoring antibiotic consumption.